Metformin Ameliorates Aβ Pathology by Insulin-Degrading Enzyme in a Transgenic Mouse Model of Alzheimer's Disease. (21st April 2020) - Lu, Xin-Yi; Huang, Shun; Chen, Qu-Bo; Zhang, Dapeng; Li, Wanyan; Ao, Ran; Leung, Feona Chung-Yin; Zhang, Zhimin; Huang, Jisheng; Tang, Ying; Zhang, Shi-Jie
Abstract : Alzheimer's disease (AD) is the most common neurodegenerative disease. The accumulation of amyloid beta (A β ) is the main pathology of AD. Metformin, a well-known antidiabetic drug, has been reported to have AD-protective effect. However, the mechanism is still unclear. In this study, we tried to figure out whether metformin could activate insulin-degrading enzyme (IDE) to ameliorate A β -induced pathology. Morris water maze and Y-maze results indicated that metformin could improve the learning and memory ability in APP swe /PS1 dE9 (APP/PS1) transgenic mice. 18 F-FDG PET-CT result showed that metformin could ameliorate the neural dysfunction in APP/PS1 transgenic mice. PCR analysis showed that metformin could effectively improve the mRNA expression level of nerve and synapse-related genes ( Syp, Ngf, and Bdnf ) in the brain. Metformin decreased oxidative stress (malondialdehyde and superoxide dismutase) and neuroinflammation (IL-1 β and IL-6) in APP/PS1 mice. In addition, metformin obviously reduced the A β level in the brain of APP/PS1 mice. Metformin did not affect the enzyme activities and mRNA expression levels of A β -related secretases ( ADAM10, BACE1, and PS1 ). Meanwhile, metformin also did not affect the mRNA expression levels of A β -related transporters ( LRP1 and RAGE ). Metformin increased the protein levels of p-AMPK and IDE in the brain of APP/PS1 mice, which might be the key mechanism of metformin on AD. In conclusion, the well-known antidiabetic drug, metformin, could be a promising drug for AD treatment.